Effectiveness of educational virtual class during Covid-19- with reference of Music online class of Fine Arts Campus, TU - Poudel, Parsuram Prasad (Journal of Fine Arts Campus, 2021)
As the Covid19 pandemic started, COVID infected nations announced to keep physical distance, affected all the human activities, as a result, educational institutions closed physically. The aim of the present research was to study the effectiveness of virtual class during Covid-19 with reference to music online class of Fine Arts Campus, TU. An online survey design was used by taking responses of 47 students of the Bachelors' program and further corresponded with 16 teachers, and 17 parents for the data collection through Google Form. The finding of the research indicates that the online mode of the educational class, with reference to practical and theory music subjects, was ineffective for students and effective for teachers and parents.